2022
DOI: 10.3389/fgene.2022.1011965
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus variants modulate the function of an enhancer upstream of TNFAIP3

Abstract: TNFAIP3/A20 is a prominent autoimmune disease risk locus that is correlated with hypomorphic TNFAIP3 expression and exhibits complex chromatin architecture with over 30 predicted enhancers. This study aimed to functionally characterize an enhancer ∼55 kb upstream of the TNFAIP3 promoter marked by the systemic lupus erythematosus (SLE) risk haplotype index SNP, rs10499197. Allele effects of rs10499197, rs58905141, and rs9494868 were tested by EMSA and/or luciferase reporter assays in immune cell types. Co-immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The levels of C/EBPB expression is also positively correlated to the SLEDAI score [38]. Pasula et al later reported that CEBPB binding to the enhancer region of tumor necrosis factor alpha-inducible protein 3 (TNFAIP3, a negative regulator of pro-inflammatory stimulation) is required for its expression, while the TNFAIP3 locus has been shown to be associated with SLE by many studies [41]. Direct involvement of CEBPB in LN was discovered by Wang's group [42].…”
Section: Cebpb Enhanced Inflammasome Activity In the Pathogenesis Of Lnmentioning
confidence: 99%
“…The levels of C/EBPB expression is also positively correlated to the SLEDAI score [38]. Pasula et al later reported that CEBPB binding to the enhancer region of tumor necrosis factor alpha-inducible protein 3 (TNFAIP3, a negative regulator of pro-inflammatory stimulation) is required for its expression, while the TNFAIP3 locus has been shown to be associated with SLE by many studies [41]. Direct involvement of CEBPB in LN was discovered by Wang's group [42].…”
Section: Cebpb Enhanced Inflammasome Activity In the Pathogenesis Of Lnmentioning
confidence: 99%
“…The gene TNFAIP3 is a likely target of the discovered enhancer, as it is a major negative regulator of pro-inflammatory nuclear factor kappa B (NF-κB) signaling, which is associated with many autoimmune diseases ( 137 ). Moreover, the risk allele (A/A) in the enhancer dramatically disrupts NF-κB binding and inhibits long-range DNA looping of the enhancer to the TNFAIP3 promoter, effectively decreasing TNFAIP3 expression and increasing IL20RA and IFNGR1 expression through TALEN (transcription activation-like effector nuclease)-mediated genome editing, HiChIP, 3C-qPCR, and dual-luciferase reporter assays ( 85 , 138 ). TNFAIP3 loss-of-function mutations result in elevated inflammatory responses, autoantibody production, and inflammatory arthritis in humanized mouse models ( 86 , 139 ).…”
Section: D Genome Disorganization In Autoimmune Diseasesmentioning
confidence: 99%
“…For example, TNFAIP3 encodes the AP20 enzyme, a known regulator of NFkB-mediated immune activation 36 and pro-IL-1β processing 37,38 . The association signals at the TNFAIP3 gene locus have been resolved to TNFAIP3 using experimental [39][40][41] or in silico 42 methods for some of the immune-mediated diseases.…”
Section: Genetic Associations Of Crispr Screening Hits With Immune-me...mentioning
confidence: 99%